Gender Differences In Perceived School Support, Self-Esteem, Academic Fatigue, And Engagement Among Nigerian Undergraduates - Pillay, Jace; Olatunbosun, Stella Oluwakemi (Academic Journal of Psychology and Counseling, 2025)
Various studies have found differences in perceived social support, self-esteem, academic fatigue, and academic engagement between men and women. Yet, at this current research location, preliminary data shows the contrary. This study examined undergraduates’ perceived school support, self-esteem, academic fatigue, and engagement in two public Nigerian universities. The cross-sectional quantitative research using the non-experimental design was employed in the study, implementing self-concordance and demands-resources theories. The population of the study was undergraduate students undertaking degree courses at two public universities in Southwest Nigeria, and participants were selected using purposive and simple random sampling techniques. An instrument tagged "School Support and Undergraduates' Self-esteem, Academic Engagement, and Fatigue Questionnaire" was used for data collection. Data were analysed using descriptive statistics and a t-test. The study's findings have shown that undergraduates’ gender influences their perceived school support and academic fatigue, with higher scores seen in male students. However, there was no significant difference in self-esteem and academic engagement between male and female undergraduates. The study recommends that efforts be concentrated on ensuring continued gender equality and gender-balanced dynamics within the school context. Implications of the study and future research suggestions are proffered.